The insider’s guide to making money in real estate : - De Roos, Dolf (John Wiley & Sons, 2005)
he Insider's Guide to Making Money in Real Estate explains why real estate is a consistently profitable moneymaker and how everyday people just like you can build their fortune regardless of their credit score or how much money they have in the bank. It's true--you don't have to be rich to invest in real estate. It's the easiest, most leveraged method for building sustainable wealth over time, and it's open to everyone.